Social Partnership in Ireland - Byszewski, Damian (Warsaw Forum of Economic Sociology, 2012)
The Irish ’Social Partnership’ is the way that corporatist accommodates the trade unions, farmers, community and voluntary sector of organisations. It was the foundation for a period of rapid growth, so-called ’Celtic Tiger’, but now most of us have little doubt that social partnership has been a key factor in the economic success of the Republic of Ireland. This simple ’tripartite’ model became a platform for negotiations between groups of various interests and aspirations. Now ’Social Partnership’ is open to criticism on ground of effectiveness but it would be a mistake to renounce to it. The important question is how democracy may be deepened within social partnership and other similar model as a potential successor. What has developed may contribute to the theorising of ’Social Partnership’ as a new form of ’multi-level’ and ’flexible’ governance and is considered as an instrument of direct participatory democracy. Social Partnership became an important process in Europe since the 1990’s and each country had surprisingly different experiences. This paper examines the origins and significance of the social dialogue in relation to a financial, fiscal and social crisis and also a distrust of legitimacy for the political elite in Ireland.